THE POWER OF WORDS: HOW VOCABULARY SHAPES THE WAY WE THINK (Multidisciplinary Journal of Science and Technology, 2025)
Language is not merely a tool for communication; it profoundly influences the way we perceive, interpret, and interact with the world. This article explores how vocabulary shapes thought processes, cognitive development, and cultural identity. Drawing upon linguistic relativity and cognitive linguistics theories, the study discusses how different languages and vocabularies determine perception, categorization, and emotional expression. It also examines the educational implications of vocabulary enrichment, emphasizing its role in critical thinking, creativity, and cross-cultural understanding. Ultimately, the power of words extends beyond expression — it forms the foundation of human consciousness and worldview.